Latin-American and Caribbean Black Women´s Day - perspective about health and wellness policies - Cruz, Isabel CF da (Online Brazilian Journal of Nursing, 2008)
This article aim was point out affirmative policies in health to prevent the occurrence of violence against Black women. An essay was conducted based on the literature.